Synchrotron imagery of phosphatized eggs in Waptia cf. W. fieldensis from the middle Cambrian (Miaolingian, Wuliuan) Spence Shale of Utah. (January 2022) - Moon, Justin; Caron, Jean-Bernard; Gaines, Robert R.
Abstract: Exceptionally preserved fossil eggs and embryos provide critical information regarding paleoembryogenesis, reproductive strategies, and the early ontogeny of early arthropods, but the rarity of preservation of both eggs and egg-bearing organisms in situ limits their use in detailed evolutionary developmental (evo-devo) studies. Burgess Shale-type deposits preserve rare instances of egg-bearing arthropods as carbonaceous compressions; however, the eggs are usually poorly preserved with no compelling evidence of embryos. We describe the first record of a brooding specimen of Waptia cf. W . fieldensis from the Spence Shale, a Cambrian (Wuliuan Stage) Burgess Shale-type deposit in northeastern Utah and southeastern Idaho. This is the first record of an egg-bearing arthropod from the Spence Shale and it exhibits two distinct modes of preservation among eggs within the single clutch: carbonization and phosphatization. Unlike the egg-bearing Burgess Shale specimens, many eggs of this Utah specimen are also preserved three-dimensionally. In addition, synchrotron radiation X-ray tomographic microscopy reveals internal distributions of mineral phases, along with potential remnants of the egg membrane and attachment structures, but, as in the Burgess Shale, no explicit traces of developing embryos. The distinct modes of preservation highlight the existence of diagenetic microenvironments within some eggs, but not in others during fossilization.